Effect of canopy cover level on solar radiation for conservation plant photosynthesis under the stand of cocoa plants. Issue 1 (April 2020) - Suhardi,; Sapsal, M T; Sjahril, R; Samsuar,
Abstract: Land degradation, which is caused by erosion, is one of the causes of the decline in the quality of cocoa plants. Vegetative soil conservation technology is one of the solutions to soil conservation on land that already has plants. The obstacle to conservation plant cultivation is its existence under the stand of plants so that solar radiation is limited for photosynthesis. This study aims to determine the level of canopy cover that can pass solar radiation for photosynthesis in conservation plants under the stand of cocoa plants. Retrieval of canopy cover data obtained through direct measurement using photo images and processed using MATLAB Image Processing Toolbox with closure approach. Solar radiation measured using the NHGH09BU Photosynthetic Active Radiation (PAR) sensor. The sensor is connected to the Arduino UNO microcontroller module. The results showed that the smaller the canopy cover, the duration of radiation that can support photosynthesis is longer. Likewise, the total active radiation for photosynthesis is inversely proportional to the percentage of canopy closure, which is the effect of the duration of active radiation. Radiation above 300 Watt/m2 occurs between 10.30 AM - 01.00 PM with the highest value 483 Watt/m2 which occurs at 11.00 AM. Total solar energy is inversely proportional to the percentage of canopy closure and is a linear relationship with R2> 0.9.